Dari Ratu Kembang Kacang hingga Berlanggam di Istana: Kiprah Waldjinah sebagai Penyanyi Istana Negara - Rafngi Mufidah; Dhanang Respati Puguh (Jurnal Sejarah Citra Lekha)
This study reveals the career path of Waldjinah, a Javanese style singer from Surakarta. The discussion emphasizes the background of childhood, education, and career journey. Waldjinah had an experience that was never forgotten and was also very influential on her career as a singer, namely when she was invited to sing at the state palace by President Sukarno and then continued until the time of President Suharto. Using historical method, this article reveals the childhood that later influenced Waldjinah's life choices. Apart from that, this study also reveals Waldjinah's progress in participating in singing competitions and led her to the State Palace. According to the findings, this study shows that Waldjinah's progress as a famous singer cannot be separated from the family education she received since childhood. In addition, Waldjinah's unyielding attitude brought her to the State Palace to reach the pinnacle of her career. This can be seen from Waldjinah's participation in Bintang Radio approximately three times, even though at the beginning of her participation she did not get the best results.